1990
DOI: 10.1111/j.1600-0447.1990.tb01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal consistency and factor structure of the Chinese Health Questionnaire

Abstract: The internal consistency and factor structure of the Chinese Health Questionnaire (CHQ) were investigated in 2 samples in Taiwan, one from 3 communities (n = 1023) and the other from consecutive attenders for health screening in a general hospital (n = 386). Cronbach's alpha coefficients were calculated to be 0.84 and 0.83 for the 12-item and 0.90 and 0.92 for the 30-item CHQ version. Four factors similarly extracted for the CHQ-30 in both samples include somatic symptoms, anxiety and worrying, social dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
118
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 15 publications
0
118
1
Order By: Relevance
“…10 The CHQ-12 also had high test-retest reliability (Pearson r = 0.77), good sensitivity (78% to 79.7%), and specificity (77% to 83.6%) in earlier studies. 8,12 Although we did not find any study that directly used the CHQ-12 to test distress level in adolescent popula-tion, the CHQ (both the English and Chinese versions) has demonstrated high validity in assessing psychological distress with young and older adolescents in the UK and Hong Kong.…”
Section: Instrumentmentioning
confidence: 73%
See 2 more Smart Citations
“…10 The CHQ-12 also had high test-retest reliability (Pearson r = 0.77), good sensitivity (78% to 79.7%), and specificity (77% to 83.6%) in earlier studies. 8,12 Although we did not find any study that directly used the CHQ-12 to test distress level in adolescent popula-tion, the CHQ (both the English and Chinese versions) has demonstrated high validity in assessing psychological distress with young and older adolescents in the UK and Hong Kong.…”
Section: Instrumentmentioning
confidence: 73%
“…9,12 A previous study 10 showed that CHQ-12 had good internal consistency (Cronbach ␣ = 0.83-0.84). 10 The CHQ-12 also had high test-retest reliability (Pearson r = 0.77), good sensitivity (78% to 79.7%), and specificity (77% to 83.6%) in earlier studies.…”
Section: Instrumentmentioning
confidence: 93%
See 1 more Smart Citation
“…Then, the potential cases (CHQ+) and non-cases (CHQ–) were categorized by the optimum cutoff point (the best compromise between high sensitivity and a low false-positive rate) of 2/3, which was based on the receiver operating characteristic curves. The consistency of the Cronbach alpha was 0.79 [24]. …”
Section: Methodsmentioning
confidence: 99%
“…This is a self-assessment tool created as a simple discriminative questionnaire to detect non-psychotic disorders, but some psychometric studies have led to the conclusion that the GHQ can measure distress as well. [11][12][13] The Polish version of the GHQ-30 has been adapted for the purpose of the present study. 14,15 The GAF scale is a unidimentional scale, used to measure general functioning and it is attached to DSM-IV classification.…”
Section: Methodsmentioning
confidence: 99%